KESWADAYAAN DAN MODAL SOSIAL MASYARAKAT DALAM PEMANFAATAN BANTUAN STIMULAN PERUMAHAN SWADAYA DI DESA SUNGAI SINTANG, KABUPATEN SINTANG - Markus, Markus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
Abstract: Self-Help Housing Stimulant Assistance (BSPS) is an Indonesian government program which aims to help low-income communities improve the quality of their homes. This program provides assistance in the form of building materials and funds to encourage people to repair or build livable houses on their own initiative and efforts. Using qualitative methods with interview, observation and documentation techniques, this research aims to describe and analyze community self-sufficiency and social capital as important elements in utilizing the BSPS program. The research results show that in the context of BSPS house building, self-sufficiency has a close relationship with social capital and the two support each other. Social networks and trust between group members also support self-sufficiency by facilitating cooperation and involvement of group members in the BSPS program implementation process. Furthermore, a high level of trust in a community can increase the ability of community members to rely on each other and share resources which is the basis of self-sufficiency, where trust allows community members to take initiative and act independently but still receive support from their community. Social capital helps in the identification and mobilization of local resources in the presence of strong networks. Self-sufficiency relies heavily on the ability of communities to find and use the resources around them where social capital plays a key role. Keywords: Self-sufficiency; social capital; utilization; Self-Help Housing Stimulant Assistance